Tinjauan Pustaka: Penggunaan Model Orlando Di Keperawatan Jiwa Gawat Darurat - Pragholapati, Andria; Fitrikasari, Alifiati; Handayani, Fitria (Jurnal Keperawatan Komplementer Holistic, 2024)
This study aims to evaluate the use of the Orlando Model in emergency psychiatric nursing through a narrative review. The Orlando model is a conceptual framework used in nursing practice to understand patient experience and provide more holistic care. In this study, we conducted a literature search across various databases and evaluated literature studies relevant to the use of the Orlando Model in emergency psychiatric nursing. The results of this narrative review show that the use of the Orlando Model in emergency psychiatric nursing can help nurses understand the patient experience holistically and provide more effective care. The Orlando model can assist nurses in identifying psychological and social problems underlying the patient's condition, as well as providing more individualized care and focusing on the patient's needs. In addition, the use of the Orlando Model can also improve communication between nurses and patients, thereby helping to build a better relationship between the two. However, there are some limitations in this literature study, such as the lack of a number of relevant studies and the limited variation in population and research settings. Therefore, further research is needed to confirm the findings from this literature study and evaluate the effectiveness of using the Orlando Model in emergency psychiatric nursing in a more comprehensive manner.